Semen Characteristics of Vaccinated Shikabrown Cocks Challenged with a Velogenic Newcastle Disease Virus - Rwuaan, J.S.; Rekwot, P.I.; Abdu, P.A.; Eduvie, L.O.; Obidi, J.A. (International Journal of Poultry Science, 2009)
Twenty-five cocks consisting of 14 red and 11 white Shikabrown cocks selected on the basis of body weight and antibody titres were infected with 0.2 ml of 106.0 EID50 of a velogenic Kudu 113 strain of Newcastle disease virus intranasally and intraocularly. Twenty-five cocks consisting of 14 red and 11 white Shikabrown cocks served as controls. Cloacal temperatures, live weights and semen samples of both control and infected cocks were taken weekly for six weeks. Semen was collected by abdominal message and evaluated for volume, colour, motility, concentration, percent live spermatozoa and percent total spermatozoa abnormalities. The semen volume of infected red cocks showed a general increase over that of control red cocks. The semen volume of the control white Shikabrown cocks was significantly (p<0.05) higher than that of the infected white cocks. The white Shikabrown cocks had higher semen volume than the red Shikabrown cocks. The red Shikabrown cocks had slightly better semen colour than the white Shikabrown cocks. The control white cocks had better (p<0.05) spermatozoa motility than the infected white cocks, while the infected red cocks had significantly (p<0.05) spermatozoa motility than the control red cocks. Generally, the white Shikabrown cocks had better spermatozoa motility than the red cocks. The spermatozoa concentration of the control white cocks was consistently higher than that of the infected white cocks; the reverse was the case with the red cocks where the spermatozoa concentration of the infected red cocks was higher than that of the control red cocks. The white cocks had higher spermatozoa concentration than the red cocks. The control white Shikabrown cocks had significantly (p<0.05) higher percent live spermatozoa than the infected white cocks. The infected red Shikabrown cocks had significantly (p<0.05) higher percent live spermatozoa than the control red cocks. The control white cocks had significantly (p<0.05) higher percent live spermatozoa than the control red cocks. The infected red and white Shikabrown cocks had higher percentage total spermatozoa abnormalities than the control red and white cocks. It can be concluded from this study that the white Shikabrown cocks had better semen quality than the red Shikabrown cocks. It is recommended that breeder cocks be routinely vaccinated against Newcastle disease to ensure that the level of antibodies is high enough to prevent adverse effects on semen quality.